Diversity and Frequency of The Kind of Lichen in Gumitir Mountain area of Jember Regency - Siti Murdiyah; Pujiastuti Pujiastuti; Rino Tri Prasetyo (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
The area of Indonesia is 1.3% of the Earth, but it has the highest level of biodiversity. Biodiversity in the environment needs to be explored. The mountain area is one of the most suitable environments for exploring biodiversity, such as the Gumitir Mountain. Gumitir Mountain has altitude around 620 meters above sea level. Gumitir Mountain has high biodiversity. Mosses (Bryophyta), ferns (Pteridophyta), till seed plants (Spermatophyta), and including Lichen was found in this area. Lichen is a mutualism symbiotic organism between fungi and green algae or blue-green algae that lives on the surface of the tree or another substrate with a variety of shapes and colours. This study aims to determine the diversity of kinds and frequencies of each kind of lichen found in the Gumitir Mountain area of Jember Regency. This research classified into exploratory research. Data retrieval is using the cruised method. Lichens are found in 20 species with Phlyctis arena (Ach.) Flot. as kind of lichen that is abundant in Gumitir Mountain Area.